Promises and perils of AI use on the tertiary educational level - Lukianets, Halyna; Lukianets, Tetiana (My University, 2023)
This article describes possible practical applications of Artificial Intelligence on the tertiary educational level both from the staff and students’ perspectives on the basis of experience gained by universities worldwide. AI usage in higher education field is analyzed on the basis of correlation between participants of educational process and the areas of innovative software application. Advantages of AI use are outlined on institutional, social and instructional levels. AI proves to be a growing and promising tool for facilitating educational processes, having obvious benefits for the education-givers and seekers, including the institutional possibilities of streamline enrollment and improved retention, organizational guidance and support of students on campus as well as educational opportunities such as better recourses management and successful online training process. Additionally, ethical considerations are raised, regarding use of AI, data management and privacy. Ця стаття описує можливі практичні застосування штучного інтелекту на рівні вищої освіти як з точки зору персоналу, так і студентів на основі досвіду, отриманого університетами в усьому світі. Проаналізовано використання ШІ у сфері вищої освіти на основі співвідношення учасників навчального процесу та сфер застосування інноваційного програмного забезпечення. Окреслено переваги використання ШІ на інституційному, соціальному та навчальному рівнях. ШІ виявляється все більш перспективним інструментом для полегшення освітніх процесів, який має очевидні переваги для тих, хто дає освіту та шукачів, включаючи інституційні можливості оптимізації зарахування та покращення утримання, організаційне керівництво та підтримку студентів у кампусі, а також освітні можливості, такі як краще управління ресурсами та успішний онлайн-навчальний процес. Крім того, піднімаються етичні міркування щодо використання штучного інтелекту, керування даними та конфіденційності.
Keywords: кафедра іноземних мов професійного спрямування; AI; institutional level; machine-learning; pedagogical guidance; personalized learning; social interaction; штучний інтелект; інституційний рівень; машинне навчання; педагогічне керівництво; персоналізоване навчання; соціальна взаємодія